Optimalisasi Kemampuan Pengolahan Dokumen Akademik Melalui Pelatihan Microsoft Word 2021 di SMP Ma’arif NU - Anggraeni, Ester Yuniar; Ayu Apriliana Maharani; Ito Setiawan (JURNAL MULTIDISIPLIN ILMU AKADEMIK, 2026)
The rapid transformation toward a digital-based education ecosystem necessitates that junior high school students possess more than just basic computer literacy; they must master professional word processing tools to support their academic journey. This study explores the implementation and impact of intensive Microsoft Word 2021 training at SMP Ma’arif NU 1 Purwokerto, a program designed to bridge the skill gap in digital document production. Utilizing a Participatory Action Research (PAR) approach, the study involved 30 students who participated in structured modules ranging from foundational interface navigation to advanced document configurations. The curriculum specifically targeted high-level skills, including complex font typography, sophisticated image manipulation for academic layouts, and crucial document security measures such as file encryption and password protection. Quantitative and qualitative evaluations reveal a significant 45% increase in students' technical proficiency. The most notable improvements were observed in the students' ability to design professional-standard report covers and execute data security protocols to protect their digital intellectual property. These findings suggest that targeted technical training effectively enhances students' readiness to produce high-quality, secure academic documents. Ultimately, this research underscores the vital role of practical software mastery in fostering broader digital literacy within the secondary education curriculum.